PENGARUH PENERAPAN MODEL PROBLEM BASED LEARNING (PBL) BERBASIS STEM PADA MATERI SUB KONSEP PERUBAHAN LINGKUNGAN TERHADAP HASIL BELAJAR PESERTA DIDIK KELAS X SMAN 11 BANJARMASIN - Husain, Naufal Shadiq; Noorhidayati, Noorhidayati; Utami, Nurul Hidayati (Tunjuk Ajar: Jurnal Penelitian Ilmu Pendidikan, 2024)
One form of learning in implementing the Merdeka curriculum is the application of the PBL-STEM model which brings students closer to real problems. The aim of this research is to examine the effect of applying the PBL-STEM model on cognitive learning outcomes in the environmental change sub-concept material. The method used in this research was quasi-experimental and non-equivalent control group. The experimental class was held in class X-F with a minimum number of students 34 people, and the control class was held in class X-D with a minimum number of students 34 people. Data was collected from pretest and posttest scores (product cognitive). In the data analysis technique, the Wilcoxon test was used for pre-test and post-test. The results of the research show that the application of the PBL-STEM model has an effect on students' cognitive learning in learning the sub-concept of environmental change in class X, 7.03 (caring), 6.78 (sharing), and psychomotor 21.2 (high category).